2019
DOI: 10.3390/agriculture9020041
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder-Based Oil Palm and Rubber Production in the Forest Region of Guinea: An Exploratory Analysis of Household Food Security Outcomes

Abstract: The Guinean government has promoted the large-scale production of industrial crops such as oil palm and rubber through the Guinean Oil Palm and Rubber Company (SOGUIPAH). Smallholder-based production of these crops has also been promoted to boost rural development but the food security outcomes are unclear. This exploratory study assesses the food security outcomes of smallholder-based oil palm and rubber production at the household level using six standardized metrics of food security. We compare households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Past studies [44][45][46][47] have adopted ETER model to analyse the impact of interventions. It is recommended that to achieve accurate estimates, at least an instrumental variable should be included in the selection variable.…”
Section: Assessing the Impact Of The Programme On Youth Agripreneurshmentioning
confidence: 99%
“…Past studies [44][45][46][47] have adopted ETER model to analyse the impact of interventions. It is recommended that to achieve accurate estimates, at least an instrumental variable should be included in the selection variable.…”
Section: Assessing the Impact Of The Programme On Youth Agripreneurshmentioning
confidence: 99%
“…What makes palm oil production one of the most desirable and accessible sources of income, with a positive impact on socio-economic development and poverty reduction, is its higher profitability and its low labour intensity (Persey et al 2011, Jelsma et al 2017, Grepalma 2020. Some studies have shown that oil palm farmers in Guinea have more stable incomes than farmers who do not grow oil palm or other cash crops (Balde et al 2019, Qaim et al 2020; furthermore, smallholders whose main source of income comes from oil palm cultivation have better financial and well-being indicators, as well as lower malnutrition rates than smallholders who do not cultivate oil palm (Dayang Norwana et al 2011, Budidarsono et al 2012).…”
Section: Sdg 1: No Povertymentioning
confidence: 99%
“…There are many new jobs and employment created by oil palm for landless laborers and rural households in Indonesia, in Mexico and Guatemala [37]. For some countries like Ghana and Guinea, there is a relative stable incomes and higher levels of food security [30,38]. Migrations is another aspect underlined by [39].…”
Section: Social Impacts In the Oil Palm Sector In Cameroonmentioning
confidence: 99%